Time course of chemokine expression and leukocyte infiltration after acute skeletal muscle injury in mice. Issue 3 (April 2015) - Nicholas, Jennifer; Voss, Joachim G; Tsuji, Joyce; Fulkerson, Nadia D; Soulakova, Julia; Schneider, Barbara St Pierre
Innate pro-inflammatory processes, such as chemokine signaling and leukocyte infiltration, predominate during the first 48 h after an acute skeletal muscle injury. However, the time course of chemokine expression and its relationship to leukocyte infiltration after acute muscle injury within this early post-injury time period has not been investigated. In this study, 46 anesthetized female C57BL/6NHsd mice underwent a closed crush injury of the gastrocnemius muscle and were euthanized 4, 8, 24 and 48 h post-injury. Microarray analysis found 14 chemokine genes to be up-regulated during this period, 12 of which are involved in macrophage or neutrophil chemotaxis, with up-regulation peaking at either 8 or 48 h. RT-PCR analysis on select chemokines confirmed the microarray activation pattern. Neutrophil infiltration patterns mirrored the time course of neutrophil-related chemokines with Gr-1-, 1A8- and 7/4-positive neutrophils infiltrating the muscle 4 h after injury, decreasing at 48 h. Conversely, gene expression and relative quantification levels of macrophage-related chemokines Ccl2 and Ccl7 peaked at 8 h, preceding the infiltration of CD68- and F4/80-positive macrophages, and protein expression of Ccl2 in the muscle. The up-regulation of other macrophage-related chemokines and their receptors peaked at 48 h post-injury.